Does the Alt‐Right still matter? An examination of Alt‐Right influence between 2016 and 2018. Issue 4 (8th July 2021) - Thompson, Jack; Hawley, George
Abstract: In this paper, we use panel data from the 2016 and 2017 waves of the Voter Study and the 2018 American National Election Studies (ANES) Pilot, to better understand the relative influence of the Alt‐Right on mainstream US politics in the Trump era. Given the degree of formal alignment between Trump and a number of key voices within the movement, we first examine the strength of the association between affect for the Alt‐Right and support for Republican Party between 2016 and 2018. We also examine relative levels of affect for the Alt‐Right among Whites between this period, tracking a number of important changes. We find that, while affect for the Alt‐Right was strongly associated with support for Republican candidates such as Trump in the 2016 election cycle, we find a somewhat weaker relationship between affect for the Alt‐Right and White support for Trump and down ballot Republican candidates in 2018. We also find that, after rising between 2016 and 2017, levels of affect for Alt‐Right appear to have declined by 2018. The results are therefore reflective of exponential rise of the Alt‐Right during the 2016 election and the movement's subsequent implosion after the 2017 'United the Right', rally in Charlottesville, VA.